2018
DOI: 10.1186/s40249-018-0433-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium yoelii infection inhibits murine leukaemia WEHI-3 cell proliferation in vivo by promoting immune responses

Abstract: BackgroundLeukaemia is a malignant leukocyte disorder with a high fatality rate, and current treatments for this disease are unsatisfactory. Therefore, new therapeutic strategies for leukaemia must be developed. Malaria parasite infection has been shown to be effective at combating certain neoplasms in animal experiments. This study is to demonstrate the anti-leukaemia activity of malaria parasite Plasmodium yoelii (P. yoelii) infection,.MethodsIn this study, the proportion of CD3, CD19, CD11b and Mac-3 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Because of the high incidence and mortality associated with colon cancer, researchers devoted to reducing mortality and improving patients' quality of life are continuously seeking new treatments to inhibit the growth, recurrence, and metastasis of colon cancer [ 34 ]. The murine model is a common model for cancer research [ 35 ], and the P. yoelii 17XNL nonlethal strain of malaria parasite can be used to infect the mice for examining its antitumor effect without causing the death of the animals [ 5 7 ]. Previously, our team and other researchers have all found that Plasmodium infection had antitumor effects on some cancers in different mouse models, but it was not clear whether it would have similar influences on colon cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the high incidence and mortality associated with colon cancer, researchers devoted to reducing mortality and improving patients' quality of life are continuously seeking new treatments to inhibit the growth, recurrence, and metastasis of colon cancer [ 34 ]. The murine model is a common model for cancer research [ 35 ], and the P. yoelii 17XNL nonlethal strain of malaria parasite can be used to infect the mice for examining its antitumor effect without causing the death of the animals [ 5 7 ]. Previously, our team and other researchers have all found that Plasmodium infection had antitumor effects on some cancers in different mouse models, but it was not clear whether it would have similar influences on colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…According to a report, a negative correlation was found between the incidence of malaria and the mortality rate of some cancers globally from 1955 to 2008 [ 4 ]. The antitumor effect of Plasmodium infection has been reported in animal studies, including lung cancer [ 5 ], hepatocellular carcinoma [ 6 ], leukemia [ 7 ], and melanoma [ 8 ]. However, it has not been reported whether Plasmodium infection can inhibit colon cancer.…”
Section: Introductionmentioning
confidence: 99%